Dimeric Transmembrane Structure of the SARS-CoV-2 E Protein - Rongfu Zhang; Huajun Qin; Ramesh Prasad; Riqiang Fu; Huan-Xiang Zhou; Timothy A. Cross (Communications Biology, 2023)
Abstract The SARS-CoV-2 E protein is a transmembrane (TM) protein with its N-terminus exposed on the external surface of the virus. At debate is its oligomeric state, let alone its function. Here, the TM structure of the E protein is characterized by oriented sample and magic angle spinning solid-state NMR in lipid bilayers and refined by molecular dynamics simulations. This protein was previously found to be a pentamer, with a hydrophobic pore that appears to function as an ion channel. We identify only a front-to-front, symmetric helix-helix interface, leading to a dimeric structure that does not support channel activity. The two helices have a tilt angle of only 6°, resulting in an extended interface dominated by Leu and Val sidechains. While residues Val14-Thr35 are almost all buried in the hydrophobic region of the membrane, Asn15 lines a water-filled pocket that potentially serves as a drug-binding site. The E and other viral proteins may adopt different oligomeric states to help perform multiple functions.